Bosnia and Herzegovina : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper examines the risks and structural weaknesses in Bosnia and Herzegovina. The paper provides an estimate of the current account adjustment required to stabilize net foreign liabilities. It uses the external sustainability approach of the Consultative Group on Exchange Rate Issues (CGER) methodology for exchange rate assessment. The paper analyzes the impact of the newly introduced borrowing rules on the longer-term debt dynamics. An overview of salient facts about unemployment in Bosnia and Herzegovina is also presented.